Iatrogenic Venous Air Embolism (VAE) in a patient secondary to contrast injection; a rare case - Ramsha Fatima Qureshi; Raisa Altaf; Faiza Hassan; Nimra Ali; Hina Naseer; Syeda Baneen Fatima (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Venous Air Embolism (VAE) can occur in patients while injecting contrast material, we have reported a case of a 26 yrs old patient who came with the complaint of abdominal pain, vomiting, and fever with no known Co-morbid. CT whole abdomen with contrast was performed and the patient was injected with contrast, which resulted in an air embolism. On administration of contrast, air is seen in the hepatic vein which was not seen on plain and delayed images. 93 ml of contrast material was intravenously injected by hand and followed by a drip infusion of 100 ml of contrast material.